Upaya Meningkatkan Kemampuan Dimensi Tiga Melalui Metode Inkuiri Pelajaran Matematika Kelas XII MAN 2 Batusangkar - Dewina, Mega (Inovan Publisher, 2025)
Learning using the inquiry/discovery method is a teaching model that encourages students to understand mathematical facts/relationships that are new to them. For example, certain patterns or formulas. This study used the inquiry method through a classroom action research (CAR) design to improve student learning achievement in mathematics with the subject of three dimensions. The sample was obtained from 30 students in Grade XII at MAN 2 Batusangkar, Lima Kaum District, Tanah Datar Regency, consisting of 10 male students and 20 female students. Data collection was carried out using observation sheets. Meanwhile, learning outcome data was collected through tests. Data analysis showed that the application of the inquiry learning model in discussing three-dimensional geometry had an effect on improving students' mathematics learning outcomes.